The Effectiveness of the Video-Assisted Problem-Based Learning Model of Doratoon Animation on Students' Understanding of Social Studies Subject Concepts in Grade VIII of SMP Negeri 6 Sengah Temila - Yonatan Novelius; Yusawinur Barella; M Zainul Hafizi; Hadi Wiyono (Proceeding of the International Conference on Global Education and Learning, 2025)
This study aims to determine the effectiveness of the Problem-Based Learning (PBL) model assisted by Doratoon animation videos on students’ conceptual understanding in Social Studies for eighth-grade students of SMP Negeri 6 Sengah Temila. This research employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The population in this study consisted of all eighth-grade students, with two classes selected as samples using a purposive sampling technique. The experimental class was taught using the PBL model assisted by Doratoon animation videos, while the control class used Canva media. The research instrument was a multiple-choice test consisting of 20 questions administered before and after the treatment to measure students’ conceptual understanding. The data analysis results showed that the average N-Gain score of the experimental class was 21.6% (low category), while the control class scored 22.6% (low category). The independent sample t-test yielded a significance value of 0.000 < 0.05, indicating a significant difference between the experimental and control classes. Therefore, the Problem-Based Learning model assisted by Doratoon animation videos was proven to be more effective than Canva media in improving students’ conceptual understanding in Social Studies. The results of this study are expected to serve as a reference for teachers in applying innovative learning media to support more interactive and meaningful learning.